2008
DOI: 10.1097/sla.0b013e318180a3c1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immunostimulating Nutrition on Infectious Complications After Upper Gastrointestinal Surgery

Abstract: Our study failed to demonstrate any clear advantage of routine postoperative immunonutrition in patients undergoing elective upper gastrointestinal surgery. Both enteral and parenteral treatment options showed similar efficacy, tolerance, and effects on protein synthesis. Parenteral nutrition composed according to contemporary rules showed similar efficiency to enteral nutrition. However, because of its cost-efficiency, enteral therapy should be considered as the treatment of choice in all patients requiring n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 46 publications
2
82
0
2
Order By: Relevance
“…However, various flaws in the design of these studies have been noted [72]. Studies finding no benefit to immunoenhanced nutrition have also been reported [73][74][75]. Further research will be required to determine if immuno-enhanced formulas improve esophagectomy outcomes.…”
Section: Immuno-enhanced Nutritionmentioning
confidence: 88%
“…However, various flaws in the design of these studies have been noted [72]. Studies finding no benefit to immunoenhanced nutrition have also been reported [73][74][75]. Further research will be required to determine if immuno-enhanced formulas improve esophagectomy outcomes.…”
Section: Immuno-enhanced Nutritionmentioning
confidence: 88%
“…The role and the effectiveness of immunonutrition in patients undergoing upper GI surgery have been studied and debated extensively in the literature [47][48][49][50][51][52][53][54][55][56]. According to a meta-analysis of 11 randomized controlled clinical trials [56] of enteral nutrition with an immuneenhancing formula that included 1009 patients, nutritional support supplemented with key nutrients (arginine, glutamine, branched-chain amino acids, nucleotides, and omega-3 fatty acids) significantly reduced the risk of developing infectious complications and reduced the overall hospital stay in critically ill patients and in patients with GI cancer.…”
Section: Immunonutrition In Gastrointestinal (Gi) Surgerymentioning
confidence: 99%
“…13,[21][22][23][24][25][26][27][28][29] In the present study, we enrolled all patients at nutritional risk who were identified by using the NRS, and no restriction on the type of operation was made, as this patient group is likely to benefit most from nutritional interventions. [6][7][8] So far, no randomized trial on IN has used the NRS before.…”
Section: Discussionmentioning
confidence: 99%